Immunoglobulin G4-related thoracic disease: clinical and radiological findings of a Turkish cohort - Alkan, Aslı; Durhan, Gamze; Yardimci, Gozde Kubra; Ozden Sertcelik, Umran; Farisogullari, Bayram; Ariyurek, Macit; Karadag, Omer; Koksal, Deniz (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and Aim: Thoracic involvement of Immunoglobulin G4-related disease (IgG4-RD) is relatively rare and may be disregarded at the time of initial diagnosis due to its asymptomatic nature. This study aimed to ascertain the prevalence and patterns of thoracic involvement in a retrospective cohort of Turkish patients with IgG4-RD. Methods: A total of 90 patients (47 males and 43 females, with a mean age of 57.7±15.5 years) diagnosed with IgG4-RD were reviewed retrospectively. All computed tomography (CT) scans were re-evaluated by two thoracic radiologists and IgG4-related thoracic disease was assessed on four compartments: The mediastinum, pulmonary parenchyma, airways, and pleura. IgG4-related thoracic disease was categorized as: definite, highly probable, probable or possible. Results: There were 64 patients who had undergone at least one thorax CT examination, and 18 (28%) were diagnosed with IgG4-related thoracic disease. The rate of IgG4-related thoracic disease increased by 20% and reached a ratio of 48.4% (n=31) after a thorough reevaluation of registry data specifically to thoracic findings. The mediastinum was the most frequently involved compartment, affecting 16 (51.6%) patients, followed by pulmonary parenchyma in 14 (45.2%) patients, and airways and pleura in 10 (32.3%) patients each. Other organ involvements were more prevalent and IgG4 levels were higher in patients with thoracic involvement. Eosinophils were significantly elevated in patients with thoracic involvement (p=0.023). Conclusions: IgG4-related thoracic disease is heterogeneous and likely to be more prevalent than currently recognized. The mediastinum is the most frequently involved compartment. It is important to assess IgG4-related thoracic disease at the time of initial diagnosis. Elevated levels of serum IgG4 and eosinophils, as well as a greater number of organ involvements may serve as indicators of thoracic involvement.